A taxonomic review of Myriocladus (Poaceae, Bambusoideae) in Brazil, including the description of a new species - Afonso, Edgar A. L.; Vasconcelos, Santelmo; Torke, Benjamin M.; Viana, Pedro L. (Brittonia, 2019)
A taxonomic treatment, based on herbarium study and field observations, is presented for the Brazilian species of Myriocladus (Poaceae, tribe Bambuseae, subtribe Arthrostylidiinae), a genus of woody bamboos restricted to geographically isolated uplands of the Pantepui region of Brazil, Venezuela, and Guyana. Of the 12 accepted species of Myriocladus, five are recorded from Brazil, of which four also occur in Venezuela. One species, M. caburaiensis, is known from a single collection from Brazilian territory near the frontier with Guyana and is described herein for the first time. We also provide a key to distinguish the five Brazilian species and illustrations of each.